Ultrasound Features of a Uterine Perivascular Epithelioid Cell Tumor (PEComa): Case Report and Literature Review - Luca Giannella; Giovanni Delli Carpini; Nina Montik; Valeria Verdecchia; Francesca Puccio; Jacopo Di Giuseppe; Dimitrios Tsiroglou; Gaia Goteri; Andrea Ciavattini (Diagnostics, 2020)
Background: Perivascular epithelioid cell tumors (PEComas) are rare mesenchymal tumors. One of the most frequent localizations of PEComas is the female genitourinary tract, and the uterus is the most involved site after the kidney. Correct preoperative diagnosis is rarely achieved due to the presence of nonspecific imaging features. We report a case of a uterine PEComa with particular reference to ultrasound’s role in characterizing this rare occurrence. Case presentation: a 45-year-old White woman came to our observation for cyclic abdominopelvic pain and chronic constipation. The pre-surgical ultrasound examination showed a heterogeneous tumor that was 4 cm in size, localized on the right anterolateral uterine wall. The mass had well-delimited borders and a central hypoechoic portion. The use of color Doppler showed a rich, irregular vasculature in the center with low impedance. The preoperative diagnostic hypothesis was of a smooth muscle tumor of uncertain malignant potential. After careful counseling, a surgical approach was decided upon, including a total laparoscopic hysterectomy with bilateral salpingectomy. The histological and phenotypical features were consistent with a uterine PEComa. At the last follow-up, two years after surgery, the patient is alive and well. Conclusions: Uterine PEComa is a rare occurrence that should be included in the differential diagnosis of uterine wall tumors. It can appear as a small uterine mass with heterogeneous echogenicity and a rich vascular pattern during an ultrasound evaluation. This diagnostic suspicion may assist in better surgical planning.